Influence of Magnesium Aluminate Nanoparticles on Epoxy-Based Intumescent Flame Retardation Coating System - Hatem Abuhimd (Coatings, 2020)
Ethylenediamine modified ammonium polyphosphate (EDA-MAPP) and charring-foaming agents (CFA) were prepared using a simple chemical method and further used to make intumescent flame retardant coatings based on epoxy resin. The content of MAPP and CFA was fixed at a ratio of 2:1. Nanoparticles of magnesium aluminate (MgAl2O4 NPs) have been introduced into the flame retardant coating formulation in various quantities to evaluate the promotional action of MgAl2O4 NPs with a flame retardant coating system. The promotional action of MgAl2O4 NPs on the flame retardant coating formulation was studied using a vertical burning test (UL-94V), limiting oxygen index (LOI), thermogravimetric analysis (TGA) and Fourier transform infra-red spectroscopy (FTIR). The UL-94V results indicated that the addition of MgAl2O4 effectively increased flame retardancy and met the V-0 rating at each concentration. The TGA results revealed that the incorporation of MgAl2O4 NPs at each concentration effectively increased the thermal stability of the flame retardant coating system. Cone-calorimeter experiments show that MgAl2O4 NPs effectively decreased peak heat release rate (PHRR) and total heat release (THR). The FTIR results indicated that MgAl2O4 NPs can react with MAPP and generate a dense char layer that prevents the transfer of oxygen and heat.